Estudando as equa??es no ensino fundamental: um caminho pela hist?ria e resolu??o de problemas - Cardoso, Patricia Costa (2024)
Mathematical knowledge is of fundamental importance in the contemporary world due to its applicability and its collaboration in the formation of critical and active citizens in the face of social issues. Faced with students? concerns and questions about the use, understanding and application of mathematics in everyday life, it is necessary to seek solutions to the challenges of a comprehensive education, in which skills and abilities are developed in order to guarantee the essential learning of basic education to which all students are entitled. The aim of this work is to guide pedagogical practice in the teaching of equations in classes in the ninth year of elementary school, covering the historical path and also using problem solving as methodological proposals for the study of 1st and 2nd degree equations, as well as suggesting an approach for introducing the teaching of linear Diophantine equations in a practical way with real-life problem situations. Three didactic sequences were developed, covering the history of mathematics and problem solving, using active methodologies and Digital Information and Communication Technologies, as proposals for implementing these pedagogical practices in the search for more meaningful and contextualized learning